2019
DOI: 10.1158/0008-5472.can-19-1034
|View full text |Cite
|
Sign up to set email alerts
|

MUC1-C Activates the NuRD Complex to Drive Dedifferentiation of Triple-Negative Breast Cancer Cells

Abstract: The NuRD chromatin remodeling and deacetylation complex, which includes MTA1, MBD3, CHD4, and HDAC1 among other components, is of importance for development and cancer progression. The oncogenic mucin 1 (MUC1) Cterminal subunit (MUC1-C) protein activates EZH2 and BMI1 in the epigenetic reprogramming of triple-negative breast cancer (TNBC). However, there is no known link between MUC1-C and chromatin remodeling complexes. Here, we showed that MUC1-C binds directly to the MYC HLH-LZ domain and identified a previ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 51 publications
10
70
0
Order By: Relevance
“…We also found that silencing MUC1-C decreases MYC occupancy ( Fig. 3d), consistent with involvement of MUC1-C in enhancing MYC transactivation complexes 23 . Functional studies performed with a BRN2 promoter-luciferase reporter (pBRN2-Luc) demonstrated suppression of activity by (i) mutating the distal, but not proximal, MYC binding site (Fig.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…We also found that silencing MUC1-C decreases MYC occupancy ( Fig. 3d), consistent with involvement of MUC1-C in enhancing MYC transactivation complexes 23 . Functional studies performed with a BRN2 promoter-luciferase reporter (pBRN2-Luc) demonstrated suppression of activity by (i) mutating the distal, but not proximal, MYC binding site (Fig.…”
Section: Resultssupporting
confidence: 84%
“…MUC1-C activates MYC expression in certain cancer cells [28][29][30] . In addition, the MUC1-C cytoplasmic domain binds directly to the MYC HLH-LZ region and, as a result, MUC1-C forms a complex with MYC on the promoters of MYC target genes 23 . Along those lines, we identified putative MYC binding sites in the BRN2 promoter ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro experiments have recently suggested that CHD4 depletion may be a therapeutic target in different types of BC, as it could lead to reduced tumor proliferation, migration, invasiveness, and growth ( 27 , 28 , 61 64 ) ( Figure 2 ). Thus, CHD4 status could determine the response of BC patients to current treatments, and pharmacological inhibition or targeting of CHD4 expression could improve the clinical outcome in breast cancer patients according to breast cancer type.…”
Section: Discussionmentioning
confidence: 99%